Response to primary canine core vaccination in 10-month-old seronegative dogs treated with three times the recommended therapeutic dose of Ilunocitinib tablets (Zenrelia™) - Genevieve M. Fent; Simona Despa; Les Gabor; Madison Earll; Erin E. McCandless; Sandra O’Kelley; Jared R. Patch; Jonathan Snyder; Stephen King (BMC Veterinary Research)
Abstract Background This study was designed to test the effect of a novel JAK inhibitor, ilunocitinib, on the response to modified live and inactivated vaccines when given at three times the label dose to healthy, vaccine-naive, seronegative, juvenile (10-month-old) purpose-bred research dogs. During the study, an outbreak of infectious diseases occurred including coccidiosis and a confirmed case of infectious canine hepatitis. Although confounded by disease, the data provides information to researchers and clinicians on a new member of this important class of therapeutics. Results Opportunistic infection by Cystoisospora canis was confirmed during the study and associated with mild to severe gastrointestinal disease. Morbidity was higher in the treated group compared to placebo controls and two treated dogs were humanely euthanized due to deterioration of overall health status. Decreased body condition and impaired CD4 T helper cell counts correlated with disease severity. After study completion, Canine Adenovirus Type-1 was identified via PCR in one dog. Despite an outbreak of concurrent disease, all dogs successfully achieved threshold titers to multivalent modified live vaccination administered on day 28. On day 88, responses to modified live booster and inactivated primary rabies vaccinations were decreased where 2/6 treated dogs versus all controls successfully responded to rabies vaccination. Lack of response was correlated to individuals with the most prominent clinical disease and lowest CD4 T helper cell counts. At the end of the treatment phase (day 88), all dogs recovered from disease and most demonstrated improved rabies titer levels by day 116. Conclusion Considering the mechanism of JAK inhibitors, it is not surprising dogs receiving three times the expected dose of drug had higher incidence of parasitic and viral disease compared to controls. In the face of these confounding infectious diseases, it was also not surprising that treated dogs had lower measures of health status correlating directly to both disease severity and inactivated vaccine response. Although confounding disease prevents a definitive conclusion regarding the original intent of the study, it was interesting that there was sufficient threshold response relating to the initial modified live vaccination across both control and Jak inhibitor treated groups administered on day 28, however this was not the primary endpoint of the study.